Fruits-Based Critical Nitrogen Dilution Curve for Diagnosing Nitrogen Status in Cotton - Feng, Weina; Li, Xiaofei; Dong, Helin; Qin, Yukun; Sun, Miao; Shao, Jingjing; Zheng, Cangsong; Li, Pengcheng (Frontiers in Plant Science, 2022)
Estimating the precise nutritional status of crop nitrogen (N) after flowering period is not only important to predict deficiency but the excess that could be revised by fertilization in future crops. Critical N dilution curves describing the critical N concentration ([N]c) in plant tissues during crop growth have been used to estimate the N status of whole plants in cotton. Little is known, however, about the critical N dilution curve for specific plant organs such as cotton fruits. The objective of this study was to verify the feasibility of fruits-based critical N dilution curve as a useful diagnostic tool for diagnosing the N status of cotton crops. A 3-year field experiment was conducted with seven N application rates (0–360 kg N ha–1) using the high-yielding cultivars Jimian 228 and Lumian 28, which differ in maturity. The relationship between fruits dry mass (DM) and N concentration ([N]) was analyzed, and a model of [N]c for cotton fruits was constructed and validated. The results showed that fruits [N]c decreased with increasing fruits DM. The critical N dilution curve based on cotton fruits was described by the equation [N]c = 2.49 × DM–0.12 (R2 = 0.649, P < 0.0001) across cultivar-years. The N nutrition index (NNI) of the fruits (NNIf) with the N dilution curve was significantly related to the NNI of shoot DM, relative yield (RY), and boll density at most sampling dates. For an NNIf of approximately 1, the RY was nearly 95%, while it decreased with a decreasing NNIf below 1. The petiole nitrate-N (NO3-N) concentration was also linearly related to the NNIf, suggesting that the NO3-N concentration in the petiole was a good predictor of the NNIf. Therefore, fruits-based critical N dilution curve and the derived NNIf values will serve as a useful diagnostic tool for diagnosing N status in cotton crops.